From Anzio to the Alps : an American soldier's story - Wells, Lloyd M. (Lloyd Manning), 1919-2000 (University of Missouri Press, 2004)
"This work is Lloyd M. Wells's firsthand account of World War II based on a journal he kept during the war, letters he sent home, and personal records, as well as recollections of people and events." "In June 1941, the twenty-one-year-old Wells was drafted into the army. He was commissioned second lieutenant after he attended OCS and was later promoted to first lieutenant with the First Armored Division. He saw action in North Africa, Italy, and Germany and was awarded the Combat Infantry Badge, the Purple Heart, and the Bronze Star." "Wells offers the reader information that has never before been provided. He tells exactly what happened to 2/7 Queens on the night of Februrary 21, 1944, when the troops came up to "the caves" at Anzio. He also depicts what happened during the last offensive in Italy and what armored infantry troops experienced on the perimeter of the attack. This book, however, is not just a story of battle actions. It is a personal story about the "old Army" and how young soldiers were transformed by it during one of the greatest upheavals in world history."--Jacket